#TITLE_ALTERNATIVE# - EDY KURNIAWAN (NIM 13101113), KADEK
In utilizing effort the geothermal energy to be electric energy optimally, modification of the standard thermodynamic cycle is one of the important alternative solution may be conducted. Combination between a gas turbine cycle and a Rankine cycle implemented in a geothermal power plant with any modification is focused in this study. Kamodjang power plant was chosen as an object of a case study in order to find realistic condition. A reliable software which is able to evaluate accurately some types of thermodynamic cycle was developed in order to make easier calculation. The software was supported with accurate thermodynamic property database. An alternative combined hybrid cycle is investigated more detail from thermodynamic aspect. The result shows that the hybrid cycles can increase the power output and efficiency in comparison with the standard Rankine cycle in the geothermal power plant. The power output increases about 89.34% and efficiency increases about 23.45 % for using R-134a as working fluid on the organic Rankine cycle. By using R-600 as organic working fluid, it performs the best one. The power output increases about 98.58% and efficiency increases about 29.49%. These results were base on the condition of gas turbine inlet temperature on 900 degrees C, pressure ratio of 20, steam heater outlet gas temperature on 350 degrees C, geothermal steam temperature on 250 degrees C, and inlet pressure of 3.5 MPa and inlet temperature of 340 degrees C in organic turbine.